University Incubators: A Pathway to Entrepreneurial Society - Olaoye Aderonke, Oloruntoba Anuoluwapo & Sunday Dorcas Kolo, Udoh Iboro Paul (Covenant Journal of Entrepreneurship, 2018)
This paper argues that universities would improve their involvement through an active and well-integrated incubation system for the advancement of viable entrepreneurial society. Based on a conceptual analysis the study examines the moving trend of universities in society from teaching to research and development, innovation, entrepreneurship and currently to enable an entrepreneurial society by enhancing entrepreneurial norms and institutional improvement. It is positively believed by researchers that the 21st century will depend on knowledge, innovation, entrepreneurship and business incubators. Nevertheless, universities are failing to contribute with full strength in research commercialization, entrepreneurship and economic growth. University incubators afford a facilitative environment for income generation by ensuring a covering with financial and legal support for a smooth collaboration between universities, business persons, government and society. In an entrepreneurial society, universities go one step ahead by configuring the instruments to enhance entrepreneurial norms and build leaders. This study also highlights the strengths and weaknesses of university incubators to promote better economic productivity. Finally the study offers some future directions for university incubators with policy recommendations.